Human Papillomavirus-Associated Cancers in Georgia, 2008-2012 - Irene Solomon; Chrissy McNamara; A. Bayakly (Georgia Southern University, 2016)
Background: High-risk human papillomaviruses (HPV) cause most anal, vaginal, vulvar, penile, and oropharyngeal cancers, and virtually all cervical cancers. In 2014, in Georgia (GA), fewer than half of adolescent females and males aged 13-17 years received the three doses of the HPV vaccine. Increasing vaccination coverage among this age group, education of adolescents in regard to HPV risks, and cervical cancer screening of adults can prevent HPV-associated cancers. Methods: The incidence of HPV-associated cancers for 2008-2012 in GA was obtained from GA Comprehensive Cancer Registry data. Case definitions for HPV-associated cancers were based on standard definitions of the Centers for Disease Control and Prevention (CDC). Data for anatomic sites known to have HPV-associated cancers, including the cervix, vulva, vagina, penis, anus, and oropharynx, were analyzed. Also derived were ageadjusted rates, age-specific incidence rates, the percentage of each cancer found attributable to HPV, and ageadjusted incidence rates by geography. Results: During 2008-2012, a total of 6,056 HPV-associated cancers were diagnosed (males, 2,408; females, 3,648). Of these, 4,629 cancers were attributable to HPV (males, 1,574; females, 3,055). The most common cancers attributable to HPV were oropharyngeal cancers among males (1,182); and cervical cancers (1,862) among females. Females living in smaller urban counties had a higher cervical cancer incidence rate than females living in metropolitan counties and metro areas (1 million or more population). Males living in rural counties had a lower oropharyngeal cancer incidence compared to the state incidence rate. Conclusions: Since HPV vaccination at age 11-12 years can prevent HPV-related cancers in adulthood, clinicians should promote HPV vaccination along with routine immunizations to adolescents. Surveillance of HPVassociated cancers using GA cancer registry data is needed to track future changes in incidence data due to administering the HPV vaccine, increasing cervical cancer screening, and educating youth in GA about HPV risk factors.